Manajemen Privasi Komunikasi Pengguna Fitur Spaces Di Media Sosial X - Acchedya Ashria Rahman; SriWijaya Herwindya Baskara Wijaya (Jurnal Komunikasi Massa, 2026)
This research examines one of the features of social media X that is frequently used for online interaction with a broad audience, namely the Spaces feature. The research aims to explore how users of the Spaces feature disclose personal information related to their romantic relationships. This study employs the Communication Privacy Management (CPM) theory proposed by Sandra Petronio, which posits that individuals have a decision-making system for determining which information is appropriate to reveal publicly (revealed information) and which should remain private (private information). A qualitative case study method was used, involving five informants who are university students in Surakarta. The findings indicate that the informants manage their privacy by selectively disclosing private information such as profile photos, identity, location, and academic details when using Spaces. In disclosing such private information, the informants also establish boundaries regarding what should not be shared with the public. By setting these boundaries, users demonstrate control over their personal information, including managing their Spaces audience to exclude irresponssible individuals. Furthermore, the informants apply dialectical management by carefully considering which information to disclose to the public in order to minimize the risk of privacy turbulence.